2016
DOI: 10.1097/jtn.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Distracted Biking

Abstract: Commuting via bicycle is a very popular mode of transportation in the Northeastern United States (US). Boston, MA has seen a rapid increase in bicycle ridership over the past decade which has raised concerns and awareness about bicycle safety. An emerging topic in this field is distracted bicycle riding. This study was conducted to provide descriptive data on the prevalence and type of distracted bicycling in Boston at different times of day. This was a cross-sectional study in which observers tallied bicyclis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 20 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…For instance, Montoro et al (2014) found that most of the road crashes involving cyclists and causing, in many cases, considerable injuries and even death, were preceded by cycling distractions. Also, Wolfe et al (2016) determined that distractions may differentially affect cyclists depending on the hour of the day, which is related to factors such as their motives to ride and the cycling intensity. Finally, Mwakalonge, White & Siuhi (2014) found that specific distractors, such as the use of electronic devices while cycling, constitute an unsafe behavior that could possibly be regulated by traffic rules, in order to avoid its potential incidence in risky road behaviors and crashes, whose odds are significantly increased by road distractions ( Goldenbeld et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Montoro et al (2014) found that most of the road crashes involving cyclists and causing, in many cases, considerable injuries and even death, were preceded by cycling distractions. Also, Wolfe et al (2016) determined that distractions may differentially affect cyclists depending on the hour of the day, which is related to factors such as their motives to ride and the cycling intensity. Finally, Mwakalonge, White & Siuhi (2014) found that specific distractors, such as the use of electronic devices while cycling, constitute an unsafe behavior that could possibly be regulated by traffic rules, in order to avoid its potential incidence in risky road behaviors and crashes, whose odds are significantly increased by road distractions ( Goldenbeld et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering statistics, cyclists represent around 7.8%–10% of all registered deaths on the road ( Montoro et al, 2014 ; Puchades et al, 2017 ). In a study on North American cyclists, Wolfe et al (2016) found that cycling distractions are more prevalent during certain hours of the day, especially around midday (40% of cyclists reporting distractions) and during morning hours (07:30 AM and 10:30 AM, with frequencies of 32.2% and 29.3%, respectively). Around 75% of fatal or serious crashes involving cyclists take place in urban areas, and approximately 10% of dead or injured cyclists are children ( RoSPA, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen percent of riders were observed wearing headphones (possibly linked to music or a cell phone). Wolfe et. al.…”
Section: E-scooter Riders Are Less Distracted By Cell Phones Found Umentioning
confidence: 99%
“…In Sweden, the prevalence was 19% in 2012, with 17.1% listening to music, 1.9% calling and .6% interacting with the phone (Adell et al 2014). In Boston, MA, USA, 31.2% of the observed bicyclists used their phones, where 17.7% used earbuds or talked on the phone and 13.5% interacted with their phones (Wolfe et al 2016). How phone use corresponds to crash risk is less known.…”
Section: Introductionmentioning
confidence: 99%